CHRO firm dinosaur versus CHRO role gorilla: the effect of CHRO company and role tenure on firms' social performance - Nina Engels; Denise Fischer-Kreer; Malte Brettel (Journal of Business Economics, 2021)
Academics and practitioners emphasize the rising importance of Chief Human Resource Officers (CHROs). CHROs act as heads of staff—they motivate the personnel and offer guidance. This study helps clarify the impact of increasingly relevant CHROs and reveals how their company and role tenure influence firms' social performance. Drawing on a multisource longitudinal dataset of S&P 500 firms, we empirically validate our hypotheses. The sample contains 283 companies with 1944 firm-year observations from 2005 to 2017 and combines manually collected top management team data with data from Thomson Reuters Datastream. Our results show that there is a negative relation between CHROs with long company tenure and firms' social performance, whereas CHROs with long role tenure positively relate to firms' social performance. We also investigate the moderating role of CEO prior experience (i.e., HR experience, education, company and role experience) on the effect of CHRO company and role tenure on firms' social performance. Surprisingly, CEO prior experience negatively moderates the relationship between CHRO role tenure and firms' social performance. Overall, this article offers novel implications for the CHRO role and uncovers a distinction between two types of CHROs: CHRO firm dinosaurs versus CHRO role gorillas.
Keywords: 650; CHRO company tenure; CHRO role tenure; Firm social performance; CEO prior experience; Upper echelons research